IMPROVEMENT OF KNOWLEDGE AND PRACTICAL SKILLS IN FAMILY DOCTORS AT THE THEMATIC IMPROVEMENT COURSE "MANAGEMENT OF PATIENTS WITH HIV/AIDS BY FAMILY DOCTORS" - Zhdan, V.M.; Shilkina, L.M.; Babanina, M.Yu. (World of Medicine and Biology, 2018)
The object of the thematic improvement course «Management of patients with HIV/AIDS by family doctors» is to improve the knowledge, to upgrade the level of formed abilities and skills while working with HIV patients and to reduce the stigma and discrimination connected with HIV. Family doctors training on HIV clinical manifestations, counseling services and testing have been described. To offer insights into a number of legal documents regulating the work of family physicians in the field of providing medical and social assistance to HIV-infected patients: doctors should perform rapid tests on the basis of primary health care centers and organize the route of the patient; institution of primary health care and/or a family doctor will prescribe antiretroviral therapy, monitor the side effects of drugs, perform prophylactic medical examination and provide palliative care.
Keywords: HIV-infection/AIDS; family doctors; distance learning; interactive training methods